2013
DOI: 10.2135/cropsci2012.03.0171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Row Spacing, Seeding Rate, and Planting Date on Establishment of Switchgrass

Abstract: T he renewable fuel standard developed by the USEPA mandates volume requirements for renewable fuels, which will continue to increase through 2022 (USEPA, 2011). Currently, corn (Zea mays L.) is the primary feedstock for ethanol production; however, increasing human population and food demands will reduce corn available for ethanol production in the future. There is a need for alternative ethanol feedstocks from nonfood plant sources that are less competitive with human food production. Biomass is an alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Foster et al (2013) reported greater lowland switchgrass yields resulting from February vs. May plantings. Based on combinations of year and location, May plantings provided slightly more consistent second-year yields (greatest in 3 of 6 and least in 1 of 6 instances), with those in June being the least consistent (greatest in 2 and least in 3 of 6 instances), and those in March being intermediate between these two.…”
Section: Discussionmentioning
confidence: 96%
“…Foster et al (2013) reported greater lowland switchgrass yields resulting from February vs. May plantings. Based on combinations of year and location, May plantings provided slightly more consistent second-year yields (greatest in 3 of 6 and least in 1 of 6 instances), with those in June being the least consistent (greatest in 2 and least in 3 of 6 instances), and those in March being intermediate between these two.…”
Section: Discussionmentioning
confidence: 96%
“…Treatments were (i) UTC, (ii) Proceed MD (prothioconazole + tebuconazole + metalaxyl), (iii) Gaucho 600 (imidacloprid), (iv) Gaucho XT [(tebuconazole + metalaxyl) + imidacloprid], (v) Proceed MD + Poncho 600 [(prothioconazole + tebuconazole + metalaxyl) + clothianidin], (vi) Proceed MD + Gaucho 600 “Low” Rate [(prothioconazole + tebuconazole + metalaxyl) + imidacloprid], and (vii) Proceed MD + Gaucho 600 “High” Rate. Plot size was 5 by 20 ft, and switchgrass was planted at 4 lb pure live seed (PLS)/acre (5 lb/acre bulk seed at 80% PLS) in early May of each year on 15 inch row spacing (Foster et al, 2013) into existing vegetation (native range pastures sprayed with glyphosate the autumn before planting) with a Hege 1000 (Colwich, KS) small plot no‐till drill. At planting, 0.4 oz/acre of FirstRate [cloransulam‐methyl: N ‐(2‐carbomethoxy‐6‐chlorophenyl)‐5‐ethoxy‐7‐fluoro(1,2,4)triazolo‐[1,5‐c]pyrimidine‐2‐sulfonamide)] and 2.0 qt/acre of glyphosate [( N ‐(phosphonomethyl)glycine] were applied to the plot area to reduce weed competition.…”
Section: Sites Seed Treatments and Data Collection And Analysismentioning
confidence: 99%
“…Although past research on improving establishment success of switchgrass has included examinations of seed size (Aiken and Springer, 1995; Smart and Moser, 1999), seeding depth (Berti and Johnson, 2013), and competition control (McKenna et al, 1991; Curran et al, 2011), most workers have focused on seed dormancy (Shen et al, 2001; Beckman et al, 1993; Haynes et al, 1997) and planting dates (Panciera and Jung, 1984; Hsu and Nelson, 1986a,b; Smart and Moser, 1997; Foster et al, 2013). Seed dormancy has been well documented in switchgrass (Parrish and Fike, 2005; Sanderson et al, 2012) and is thought to be a common cause of establishment failures; up to 2 yr of after ripening may be required for this species to become germinable (Burson et al, 2009).…”
mentioning
confidence: 99%